Evaluation of blood pressure and NT-proBNP in pugs with and without clinical signs of Brachycephalic Obstructive Airway Syndrome - Mach, Rebekka; Wiegel, Pia Saskia; Bach, Jan-Peter; Beyerbach, Martin; Levicar, Charanthorn; Nolte, Ingo (Frontiers in Veterinary Science, 2022)
Brachycephalic Obstructive Airway Syndrome (BOAS) is a pathologic condition of the upper airways, frequently occurring in dogs of brachycephalic breeds including pugs. It has been suspected that BOAS may be associated with cardiovascular changes and an increased risk for hypertension. The cardiac biomarker NT-proBNP can help to differentiate cardiac from non-cardiac respiratory distress. A possible influence of BOAS on NT-proBNP values has not been investigated, however. The aim of the current study was to examine blood pressure and NT-proBNP levels in pugs with and without clinical signs of BOAS and compare them to values of mesocephalic dogs. For this purpose, 62 pugs and ten mesocephalic dogs serving as control group (CG) were prospectively examined in this study. Pugs were examined for clinical signs of BOAS at rest and after a submaximal fitness test, and a functional BOAS grading was applied. Blood pressure (BP) was measured at the beginning and end of the study day and NT-proBNP values were obtained before and after exercise. Measured values of pugs with different degrees of clinical impairment due to BOAS were compared among each other as well as to the CG. In terms of systolic, mean, diastolic BP, and NT-pro BNP, there was no statistically significant difference between pugs with different levels of severity of BOAS and dogs in the CG. BP values were significantly lower at the second measurement at the end of the study day. NT-proBNP measurements were significantly higher after exercise. BP and NT-proBNP values in all groups were in agreement with commonly used reference ranges. In conclusion, BP and NT-proBNP values did not differ between mesocephalic dogs and pugs with different levels of severity of BOAS but between the measurement times. Thus, in the present study, excitement and exercise seemed to have a greater influence on BP and NT-proBNP values than presence of BOAS symptoms or breed. Discovered values show that the commonly used reference ranges for BP and NT-proBNP are applicable in pugs. This indicates that NT-proBNP can be used to differentiate between cardiac and non-cardiac respiratory distress even in pugs with clinical symptoms of BOAS.